Validation of Child Health Status Questionnaire for Thai School-Aged Children. (December 2016) - Sriboonyawattana, N.; Tiansawad, S.
Abstract : Background: Perceived child health status is an important factor related to physical activity of school-aged children with congenital heart disease after corrective surgery; however, currently there is no instrument to measure it in Thailand. Objective: To validate a new instrument, the Child Health Status Questionnaire for Thai children that consists of two forms; Form I assesses child health status as perceived by the children and Form II assesses child health status as perceived by parents. Methods: The comparative, correlational design was employed. Construct validity was examined by contrast group technique and concurrent validity was tested through correlation with child's quality of life. One hundred and sixty children with congenital heart disease were purposively recruited from the cardiology clinic of one hospital; 80 were those after corrective surgery (group A), and 80 were waiting for the surgery (group B). Moreover, 160 parents of the children in both groups participated in the study. Instruments included two forms of the Child Health Status Questionnaire for Thai children and Thai Quality of Life in Children. Data were analyzed using independent t-test, and Pearson's correlation. Results: Mean scores of child health status as perceived by children in groups A and B were significantly different (t = 6.899, p < 0.001). There was also a significant difference between mean scores of child health status as perceived by parents of the two groups (t = 4.250, p < 0.001). Self-rated child health status was positively correlated with quality of life in both groups (r = 0.304, p < 0.05; r = 0.348, p < 0.05). Significantly positive relationships were also found between parent-rated child health status and quality of life of children in both groups (r = 0.396, p < 0.05; r = 0.650, p < 0.001). Conclusion: These findings provide evidence of validity of the Child Health Status Questionnaire for Thai children. It is recommended that this measure be used in further research and clinical practice among Thai school-aged children with congenital heart disease.